Improving Understanding of The Concept of Magnetic Properties Through The Guided Discovery Learning Model at Sd N 1 Tegalgondo - Dwi Zuliyani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The formulation of the problem in this study is "Can the application of the guided discovery learning model improve understanding of the concept of magnetic properties of class VI SD N 1 Tegalgondo in 2020/2021?" The purpose of the study was to determine the increase in understanding of the concept of magnetic properties in class VI SD N 1 Tegalgondo in 2020/2021. The type of research used was classroom action research (PTK) with the research subject, namely grade VI students totaling 29 people. This research was carried out in a cycle and each cycle consisted of 4 stages, namely the stages of planning, action, observation, and reflection. Based on the results of the research in cycle I shows that students who get a score above the KKM are 18 people with a percentage of 62%. This has not reached the expected performance indicators, so further action is taken to cycle II. In the second cycle, there was an increase, there were 24 students who scored above the KKM with a percentage of 82%. The results in cycle II have reached the specified performance indicators, so it can be concluded that the guided discovery learning model can improve students' understanding of the properties of magnetism in class VI SD Negeri 1 Tegalgondo, Wonosari District, Klaten Regency.